2021
DOI: 10.1519/jsc.0000000000003245
|View full text |Cite
|
Sign up to set email alerts
|

Comparision of Low and High Volume of Resistance Training on Body Fat and Blood Biomarkers in Untrained Older Women: A Randomized Clinical Trial

Abstract: Cunha, PM, Tomeleri, CM, Nascimento, MA, Mayhew, JL, Fungari, E, Cyrino, LT, Barbosa, DS, Venturini, D, and Cyrino, ES. Comparision of low and high volume of resistance training on body fat and blood biomarkers in untrained older women: a randomized clinical trial. J Strength Cond Res 35(1): 1–8, 2021—The purpose of this study was to compare the effects of resistance training (RT) performed with 2 different volumes on body fat and blood biomarkers in untrained older women. Sixty-five physically independent old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 37 publications
3
43
1
1
Order By: Relevance
“…However, the hypothesis that these occurred due to possible overtraining should not be dismissed. Although we opted for using a relatively high volume in the 24 weeks of RT because we had observed that this seems to be ideal for inducing optimal adaptations in the outcomes studied herein for this population [12,[23][24][25][26][27][28], the use of such training protocol might have exceeded the ideal training dose for some participants. Moreover, the presence of the ALT group, which performed the same EO throughout the 24 weeks of RT, allows us to believe that simply changing the EO after a 12-week training period does not influence the responses to training.…”
Section: Discussionmentioning
confidence: 99%
“…However, the hypothesis that these occurred due to possible overtraining should not be dismissed. Although we opted for using a relatively high volume in the 24 weeks of RT because we had observed that this seems to be ideal for inducing optimal adaptations in the outcomes studied herein for this population [12,[23][24][25][26][27][28], the use of such training protocol might have exceeded the ideal training dose for some participants. Moreover, the presence of the ALT group, which performed the same EO throughout the 24 weeks of RT, allows us to believe that simply changing the EO after a 12-week training period does not influence the responses to training.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that increases in strength are more dependent on the intensity of load, while muscle hypertrophy is related to the RT volume [ 12 , 13 , 14 , 15 , 16 ]. However, the best approach to improve CVD risk factors in older women is still unknown [ 6 , 7 , 17 , 18 ]. Recently, our group showed that traditional RT, even at low volume (1 set per exercise, 10–15 repetitions-maximum (RM), 3x/week–non-consecutive days) improved total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), glucose (GLU), and C-reactive protein (CRP) in untrained older women [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group showed that traditional RT, even at low volume (1 set per exercise, 10–15 repetitions-maximum (RM), 3x/week–non-consecutive days) improved total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), glucose (GLU), and C-reactive protein (CRP) in untrained older women [ 19 ]. Moreover, we observed that performing a higher volume (3 sets per exercise, 10–15 RM) resulted in greater improvements [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance training is a popular and convenient form of exercise and its positive effects on anthropometric/body composition status in women of different ages and with various health conditions have already been documented [46,47]. In our study, we applied organized circuit weight training as a form of resistance training.…”
Section: Positive Effects Of Endurance and Resistance Training On Antmentioning
confidence: 99%